A Computational Investigation of Wheel and Underbody Flow Interaction - Koitrand, Sofie; Rehnberg, Sven (My University, 2013)
The use of moving ground and rotating wheels (MVG&RW) when testing road vehicles in wind tunnels have previously been shown to largely affect the results, however it is still not the standard test prodecure for many manufacturers. This also means that simulations are set up to match the static behaviour of the experimetal tests. However, when most companies today turn their efforts to the underbody of the vehicle in an effort to improve aerodynamics, stationary conditions are no longer adequate. This report aims at investigating how the rotation of the front and rear wheels in combination of moving ground influence the local, as well as the global, flow fields and especially the wake behind the vehicle, by the use of Computational Fluid Dynamics (CFD). Two different vehicle models based on the same platform, namely the Jaguar XF Saloon and Sportbrake, are used to set up eight different cases for each vehicle. The research has been set up to enable comparison with earlier experimental research. The results are divided into three groups giving the results due to the addition of a moving ground, rotating front wheels and rotating rear wheels. By adding a moving ground the drag and front lift increase noticeably, whereas the rear lift decreases significantly. The addition of front wheel rotation has little effect on the global results, whereas the addition of rear wheel rotation largely decreases both the drag and the rear lift. By adding these three groups up largely the same results are achieved as when comparing the fully stationary cases to the cases with MVG&RW conditions, namely that the addition of MVG&RW conditions noticeable reduces the drag and the rear lift, whereas front lift hardly changes.
Keywords: Energi; Transport; Grundläggande vetenskaper; Hållbar utveckling; Strömningsmekanik och akustik; Energy; Transport; Basic Sciences; Sustainable Development; Fluid Mechanics and Acoustics